A note on the Optimal Periodic Pattern (OPP) algorithm for the system in which buyers periodically order from a vendor - Bylka, Stanisław; Krupa, Andrzej (Computers & industrial engineering, 2018)
•We revisit research contributed by Afzalabadi et al. (2016).•For the algorithm two counterexamples with appropriate comments are presented.•We provide conditions for optimal ordering policy in the periodic demand case. In this study, we revisit research contributed by Afzalabadi et al. (2016), where a lot size problem for discrete periodic demand case was considered. Our note indicates incorrectness of the main thesis that the OPP algorithm finds the optimal solution in a finite number of steps. Numerical counterexamples with appropriate comments are presented. We also provide a reformulation of the model and proper conditions for optimality.